PROSEDUR SURVEI PEMETAAN BAWAH LAUT UNTUK PERENCANAAN PEMASANGAN SISTEM KABEL LAUT INDONESIA CABLE BASE TSUNAMIMETER (INA-CBT) - Dwi haryanto; Hendra Kurnia Febriawan; Yudo Haryadi; Rahadian Rahadian; Djunaedi Muljawan (Oseanika, 2020)
[Seabed Mapping Prosedure for Indonesia Cable Based Tsunamimeter (Ina-CBT) Installation Planning] Indonesia, which is located in the “Pacific Ring of Fire”, is a potential country for tsunami disaster. BPPT has developed technologies for tsunami early warning system is known as the Indonesia Cable Based Tsunameter (Ina-CBT). In 2020, BPPT will initiate four marine cable route survey in four locations where have a large potential of tsunami, namely: Labuan Bajo segment, Rokatenda segment, Makassar strait segment and the Cilacap - Krui segment. To support this project, marine cable route survey is mandatory to obtain the seabed characteristic along the route. This characteristic is necessary to obtain the suitable submarine cable route and avoid hazards during the installation and maintenance. This paper describes the procedures of Ina-CBT marine cable route survey. These procedures include scope of survey, methods, survey vessel and equipment, data processing, and reporting. It is expected that this paper could serve as reference guide to carry out a high-quality marine cable route survey, which can produce an optimum cable route and suitable cable type for the Ina-CBT development. Keywords: Tsunami, Ina-CBT, survey procedure, seabed mapping, cable route.